What companies can learn from unicorn startups to overcome the COVID-19 crisis (INMR - Innovation & Management Review, 2023)
Objective. To search measures that unicorn startups have implemented during the pandemic and show what lessons can be learned to help entrepreneurs and small and medium businesses to overcome the crisis. Design/methodology/approach. The method is a multiple case study with five unicorn startups. We collected data through interviews and analyzed them by the content analysis technique. Results. They show that the pandemic affects negatively unicorns’ businesses; that a digital business model innovation affects them positively; and that innovations moderate positively the negative impact of the crisis. Limitations/research implications. Most interviewees hold operational positions. Practical implications. Three actions stand out to overcome the crisis: adoption of new digital platforms; strategies to increase the network of partners; and adaptations in the provision of payment services. Originality/value. The cases show that entrepreneurs and SMEs need to develop capabilities to innovate in their business models, and digitalization is a solution to face the crisis and overcome it in the future.